The perception of academic administrators towards the principles of educational leadership in higher education institution: a case study in kuliyyah of economics and management sciences, IIUM. - Salleh, Mohamad Johdi; Al-Hasani, Syed Mahbubul Alam (2009)
The study presents the perception of academic administrators on the basic principles of educational leadership which can be applied by academic administrators in higher education institution. The aim of the study was to identify the effective principles that would increase the level of effectiveness in academic works. A survey method was used to collect data. A set of questionnaire were distributed to academic administrators at the Kulliyah of Economics and Management Sciences, International Islamic University Malaysia (IIUM). Findings of the study revealed that academic administrators corroborated that principles of educational leadership could help enrich excellence in higher education institutions. It is also found that the principles of educational leadership are applicable in effectuating academic administrators' leadership qualities in higher education institutions.